2017
DOI: 10.1182/bloodadvances.2017011221
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the maturation of human monocytes into immunosuppressive macrophages

Abstract: • NF-kB and Akt regulate human monocyte into macrophage differentiation; p38 MAPK and PTGS2 promote the generation of suppressive macrophage.• The Toll-like receptor 2/1 agonist PAM3 induces human monocytes to mature into immunosuppressive macrophages in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 56 publications
(82 reference statements)
4
22
0
Order By: Relevance
“…Hence, efforts to increase the frequency of immunosuppressive M2-like macrophages represents a potentially useful strategy for the treatment of SLE. Our lab previously showed that the TLR2/1 agonist PAM3 was unique among TLR ligands in promoting the generation of M2-like macrophages from normal human monocytes [14,15]. This work extends those findings to show that PAM3 similarly induces monocytes from lupus patients to preferentially differentiate into M2-like macrophages.…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…Hence, efforts to increase the frequency of immunosuppressive M2-like macrophages represents a potentially useful strategy for the treatment of SLE. Our lab previously showed that the TLR2/1 agonist PAM3 was unique among TLR ligands in promoting the generation of M2-like macrophages from normal human monocytes [14,15]. This work extends those findings to show that PAM3 similarly induces monocytes from lupus patients to preferentially differentiate into M2-like macrophages.…”
Section: Introductionsupporting
confidence: 76%
“…10 5 purified monocytes/well were seeded into 96-well flat bottom plates (Corning) and stimulated for 5 days at 37°C with 1 μg/ml PAM3CSK4 (PAM3) (Invivogen), 250 ng/ml MCSF (Miltenyi Biotec), 250 ng/ml IFNγ (Miltenyi Biotec) or 1 μl/ml R848 (Invivogen). Previous studies established that these were the optimally stimulatory concentrations of each agent ( [14,15] and data not shown). Cells were maintained in medium consisting of RPMI 1640 (Lonza) supplemented with 2% heat-inactivated fetal calf serum 25 nmol/L HEPES, 1 mmol/L sodium pyruvate, non-essential amino acids (NEAAs) and 0.0035% 2mercaptoethanol (2-ME).…”
Section: Isolation and Differentiation Of Human Monocytesmentioning
confidence: 69%
See 1 more Smart Citation
“…PAM3 induces murine monocytes to mature into M2 macrophages over four days in vivo {data not shown, section 4.2}. Of note, BMDM cultured with PAM3 for four days in vitro primarily generate M1 macrophages [30][31][32] .This differs from the effect of PAM3 on peripheral blood human monocytes ex vivo and murine monocytes in vivo, where this TLR agonist preferentially generates M2 rather than M1 macrophages 10,18,19 . Other TLR 2/1 agonists also induce the generation of immunosuppressive macrophages whereas ligands that interact with TLR2/6 heterodimers (such as FSL-1) do not (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…normal murine and human monocytes to preferentially mature into M2 macrophages 18,19 . As an excess of M1 macrophages can contribute to the pathogenesis of colitis 15 , the possibility that the protective activity of PAM3 was mediated via an increase in the number of M2 macrophages was examined.…”
Section: Effect Of Pam3 On M2 Macrophage Frequency Previous Studies mentioning
confidence: 99%